1994
DOI: 10.1111/j.1399-302x.1994.tb00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Macaca fascicularis as a model in which to assess the safety and efficacy of a vaccine for periodontitis

Abstract: We have assessed Macaca fascicularis as a potential model in which to test the efficacy and safety of a vaccine for periodontitis. Twenty-eight animals were surveyed and 20 studied in more detail. Clinical periodontal status was assessed, the subgingival microflora analyzed especially for the presence and proportions of Porphyromonas gingivalis and titers and avidities of serum antibodies reactive with P. gingivalis measured. Probing depths ranged from 0.90 mm to 3.80 mm, Gingival Index scores from 0.00 to 4.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…This evidence led to further experimental use of vaccines to affect PD in the same animal model using a vaccine containing formalinized P. gingivalis (monkey strain) as antigen. Persson et al (1994) demonstrated a significant reduction in alveolar bone loss and significantly lower proportions of P. gingivalis in the subgingival flora of vaccinated animals having high levels of opsonic anti-P. gingivalis antibody. These observations suggested that a mechanism of immune protection may be enhanced opsonization, phagocytosis, and killing of P. gingivalis or other relevant organisms.…”
Section: Antibodies Can Influence Periodontal Microorganismsmentioning
confidence: 95%
See 3 more Smart Citations
“…This evidence led to further experimental use of vaccines to affect PD in the same animal model using a vaccine containing formalinized P. gingivalis (monkey strain) as antigen. Persson et al (1994) demonstrated a significant reduction in alveolar bone loss and significantly lower proportions of P. gingivalis in the subgingival flora of vaccinated animals having high levels of opsonic anti-P. gingivalis antibody. These observations suggested that a mechanism of immune protection may be enhanced opsonization, phagocytosis, and killing of P. gingivalis or other relevant organisms.…”
Section: Antibodies Can Influence Periodontal Microorganismsmentioning
confidence: 95%
“…Parenteral immunization Enhanced bone loss in all immunized Ebersole et al (1991) Whole cells from P. gingivalis Parenteral immunization Reduced P. gingivalis, less bone loss Persson et al (1994) Passive monoclonal anti-P. gingivalis in humans…”
Section: Whole Cells From Prevotella Intermediamentioning
confidence: 97%
See 2 more Smart Citations
“…They are products from natural or synthetic origin with different chemical characteristic and mechanism of action (1,9,13,14,16,17,18,19,23).…”
Section: Introductionmentioning
confidence: 99%